MICROCIRCULATION IN CHRONIC HEART FAILURE PATIENTS TREATED WITH ACE INHIBITORS AND DIURETICS - Yu. I. Gurfinkel; M. I. Kudutkina; L. M. Parfenova; V. A. Orlov (Российский кардиологический журнал)
Chronic heart failure (CHF) is a complex clinical syndrome, which can result in structural and/or functional cardiac disturbances, decreased ventricular pump function, and inadequate cardiac ejection. This study was aimed at investigating microcirculation features in CHF patients, as well as evaluating the effects of treatment with ACE inhibitors, diuretics, and anti-aggregants on microcirculation parameters (assessed by computerized nailfold capillaroscopy) among patients with normal and low ejection fraction (EF). The study included 58 participants: 20 healthy volunteers without cardiovascular disease (mean age 52,6±6,6 years; mean EF 63,1±4,5%); 36 patients with coronary heart disease (CHD) and myocardial infarction, arterial hypertension, and CHF in anamnesis; and 2 patients with dilated cardiomyopathy. All patients were divided into two groups, by EF values. Group I included 22 individuals (12 men, 10 women; mean age 63,2±9,4 years) with EF >52%. Group II included 16 people (11 men, 5 women; mean age 62,9±8,5 years) with EF <52%. The patients received enalapril (20 mg/d), acetylsalicylic acid (125 mg/d), and furosemide (40 mg twice a week). Microcirculation parameters (perivascular zone area, capillary blood flow velocity, arterial, intermediate, and venous diameters, and “sludge” phenomenon) were assessed at baseline and after 2 weeks of the treatment. The study results demonstrated the potential of non-invasive computerized nailfold capillaroscopy for microcirculation assessment in CHF patients. This method allowed the authors to identify the microcirculation features typical for CHF: 1) increased perivascular zone area, compared to healthy controls; 2) increased ratio “venous diameter / arterial diameter”; 3) reduced capillary blood flow velocity; 4) and “sludge” phenomenon.